The The Effect of Profitablity, Capital Intensity, Form Size, and Corporate social Responsibility (CSR) on Tax Aggressiveness - Fatimah Fatimah; Atiyatul Nur Afriayani Azizah; Acep Komara (Interdisciplinary Social Studies, 2025)
This study aims to re-examine the effect of profitability, capital intensity, firm size, and corporate social responsibility (CSR) on tax aggressiveness. This study was conducted in response to inconsistent findings in previous research and to strengthen the conceptual understanding of the factors influencing aggressive tax reporting behavior. The object of this research is manufacturing companies in the food and beverage sub-sector listed on the Indonesia Stock Exchange (IDX). Out of 35 companies that met the criteria, 25 were selected as the sample over a three-year observation period, resulting in 75 observational data points. Data were collected through documentation studies by accessing financial reports, annual reports, and sustainability reports available on the official IDX website (www.idx.co.id). The variables examined include profitability, firm size, capital intensity, CSR, and tax aggressiveness. The analytical method used in this research is multiple linear regression, preceded by classical assumption tests and followed by hypothesis testing. The results show that profitability has no significant effect on tax aggressiveness. In contrast, capital intensity and firm size have a significant positive effect on tax aggressiveness, while CSR has a significant negative effect on tax aggressiveness. These findings are expected to serve as a reference for company management and policymakers in designing more transparent and ethical tax management strategies.